Comparing Nonopioids Versus Opioids for Acute Pain in the Emergency Department: A Literature Review. (January 2021) - Sin, Billy; Sikorska, Gabriela; YauLin, Joi; Bonitto, Rianne A.; Motov, Sergey M.
Abstract : Background: Pain is the most common reason for patient visits in the emergency department (ED). Opioids have been long considered the standard of care for acute pain in the ED. Because of the opioid crisis, investigation and implementation of novel practices to manage pain is needed. The use of various nonopioids has been suggested as a plausible alternative to opioids, with emerging literature to support its use for acute pain in the ED. Study Question: To evaluate the safety, efficacy, opioid-sparing effects of nonopioids in patients who present with acute pain in the ED. Data Sources: We systematically searched PubMed and EMBASE (July 1970 to January 2019). Study Design: Randomized controlled trials that evaluated nonopioids versus opioids in the ED were eligible. The clinical outcomes measured were change in pain scores compared with baseline, the incidence of adverse events, and use of rescue analgesia. Results: Twenty-five randomized controlled trials that evaluated the use of nonopioids in 2323 patients [acetaminophen (APAP) (n = 651), diclofenac (n = 547), ketamine (n = 272), ketorolac (n = 225), lidocaine (n = 219), ibuprofen (n = 162), ibuprofen & APAP (n = 162), hydroxyzine & dihydroergotamine (n = 85)] met inclusion criteria. Four trials found significant greater reductions in pain scores, favoring nonopioids. In all trials, the duration of pain relief provided by nonopioids was not sustained over an extended period. Eighteen trials reported no significant differences in reduction of pain scores. Two trials reported improved pain reduction with opioids and one trial reported noninferiority. Conclusions: Evidence from primary literature suggests that nonopioids could be a feasible alternative to opioids for management of acute pain in the ED as it is effective, safe, and decreases the need for rescue analgesia. Abstract : Supplemental Digital Content is Available in the Text.